FACTORES DETERMINANTES DE LA MOVILIDAD HUMANA DEL SECTOR RURAL AL URBANO Y SU EFECTO EN EL DESARROLLO SOCIO - ECONÓMICO DEL CANTÓN LOJA, PROVINCIA DE LOJA, PERIODO 2001- 2016 - Romero Tandazo., Gianela Carolina (2019)
Internal migration, referring to the movement of people from rural areas to large cities, who seek to improve their economic situation, however, the vast majority of these people have not obtained job offers, which has affected these people will be established in the peripheries of cities forming the so-called "poverty belts", there the importance of the study of internal migration, particularly those that go in a rural-urban sense, and where the focus of attention is the migrant individual and the reasons why They motivated him to make that decision. Therefore, the general objective of this work is to establish the determinants of human mobility and its effect on the socio-economic development of the Loja canton, Loja province, Period 2001 - 2016. This research was carried out taking as main base to the population of the 13 rural parishes of the Loja canton. Obtaining as a main result that: During the period 2001-2016, the Loja canton had an average urban-rural distribution of approximately 58% and 42%, respectively, the cantonal population has almost doubled up to five times, mainly due to the high migratory process of the rural one. Likewise, 41,15% of the population mentions that migration directly affects the supply of labor, while 28,65% mention that migration causes a decrease in the sale prices of agricultural products, likewise 27,34% consider that the migration causes an abandonment of the land dedicated to the crop, on the other hand, 2,86% indicate that the agricultural production is of low productivity.